2017
DOI: 10.1371/journal.pone.0190456
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA depletion by ethidium bromide decreases neuronal mitochondrial creatine kinase: Implications for striatal energy metabolism

Abstract: Mitochondrial DNA (mtDNA), the discrete genome which encodes subunits of the mitochondrial respiratory chain, is present at highly variable copy numbers across cell types. Though severe mtDNA depletion dramatically reduces mitochondrial function, the impact of tissue-specific mtDNA reduction remains debated. Previously, our lab identified reduced mtDNA quantity in the putamen of Parkinson’s Disease (PD) patients who had developed L-DOPA Induced Dyskinesia (LID), compared to PD patients who had not developed LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 95 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…EtBr is widely used to generate ρ0 cell lines with low mtDNA levels for investigation of the roles of mtDNA in inflammasomes and cGAS‐STING axis (Yu et al , 2020; Wang et al , 2021). EtBr treatment also has profound effects on cellular homeostasis, including increased intracellular ROS level, glycolysis, and reduced autophagic level (Nacarelli et al , 2014; Warren et al , 2017). Of note, increased ROS level and glycolysis as well as reduced autophagic level promote the activation of NLRP3‐inflammasome (Zhou et al , 2011; Xie et al , 2016; Zhong et al , 2016), whereas lower mtDNA level blocks NLRP3‐inflammasomes activation (Zhong et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…EtBr is widely used to generate ρ0 cell lines with low mtDNA levels for investigation of the roles of mtDNA in inflammasomes and cGAS‐STING axis (Yu et al , 2020; Wang et al , 2021). EtBr treatment also has profound effects on cellular homeostasis, including increased intracellular ROS level, glycolysis, and reduced autophagic level (Nacarelli et al , 2014; Warren et al , 2017). Of note, increased ROS level and glycolysis as well as reduced autophagic level promote the activation of NLRP3‐inflammasome (Zhou et al , 2011; Xie et al , 2016; Zhong et al , 2016), whereas lower mtDNA level blocks NLRP3‐inflammasomes activation (Zhong et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that ethidium bromide would not only act as a mutagen in microorganism, but also might induce mutations in higher plants and mammals (Dujardin & Dujon, ; Hayakawa et al, ; Levy & Ashiri, ). Primary cultured neurons treated by ethidium bromide (EtBr) present the consequences of mitochondrial DNA (mtDNA) depletion, which dramatically reduces mitochondrial function and can be used as a method of mouse mtDNA mutagenesis for modeling human pathological conditions (Fayzulin et al, ; Warren, Aicher, Fessel, & Konradi, ; Yu et al, ). Our preliminary experiment indicated that our siRNA tagging technology does not show any cytotoxicity on PC‐3 cell, even at very high tagging concentration (10 μM of the tags).…”
Section: The Cholesterol Tagging Technologymentioning
confidence: 99%
“…mtDNA copy number varies by cell (10) and by developmental stage (11,12), and depends on the dynamic equilibrium between mtDNA synthesis and degradation. As reported, while a decreased mtDNA copy number or mtDNA depletion may break cellular mitochondrial function and result in many diseases, an increased mtDNA copy number has a protective effect (6,1315). Given the highly active and vulnerable nature of hair cells, increasing their mtDNA copy number is a potential way to enhance their survival.…”
Section: Discussionmentioning
confidence: 86%